Male with Long Standing Heart Failure and Left Bundle Branch Block with Acute Chest Pain: Is It Needed for Urgent Revascularization? - Fahmy Rusnanta; Mohammad Saifur Rohman; Setyasih Anjarwani; Ardian Rizal (Universitas Brawijaya, 2020)
BACKGROUND: Patients with acute heart failure and left bundle branch block (LBBB) presenting acute chest pain have many clinical challenges to perform diagnostic and therapeutic process. Recent recommendations stated that the patients with LBBB (new or presumably new) should be performed early revascularization, many of clinical controversies occur due to scientific gaps between current evidence and recommendations. It has led to reviewing other approach to assess this setting.CASE SUMMARY: A 46-year-old man with previous history of dyspnea (long standing heart failure) came to our hospital with recurrent chest pain and acute heart failure. ECG showed LBBB suggesting acute myocardial infarction (excessive discordance in precordial lead). He had normal serial cardiac enzyme with on going ischemia symptom. He had been decided to not perform urgent reperfusion therapy. After five days hospitalization, he discharged home with medicines.DISCUSSION: This case report provides an example of reviewing existing algorithm to assess acute chest pain in congestive heart failure, regardless of ST segmen deviation in LBBB. Further research is needed to establish the clinical outcome for these patients underwent reperfusion strategy.